276 Enterobius vermicularis colitis in children. (11th October 2021) - Mašić, Mario; Hojsak, Iva; Jadrešin, Oleg; Kolaček, Sanja; Mišak, Zrinjka
Abstract : Objective: Infestation with pinworm (Enterobius vermicularis) is common in young children, and the most common typical symptoms are perianal itching, nocturnal restlessness, and irritability. Although the clinical presentation is usually mild or completely asymptomatic, the infestation rarely can present with non-specific colitis, weight loss, and the formation of perianal abscesses or granulomas. Methods: We retrospectively analyzed data (including medical history, age, sex, anthropometric characteristics, laboratory parameters, macroscopic and microscopic findings of ileocolonoscopy) of all patients with macroscopically proven Enterobius vermicularis. These patients were referred for diagnostic workup due to suspected inflammatory bowel disease or a bleeding polyp, from January 2010 to January 2020 at the Children's Hospital Zagreb. Results: We performed 606 ileocolonoscopies in the above mentioned period due to suspicion of chronic inflammatory bowel disease or a bleeding polyp, and E. vermicularis was identified macroscopically in 10 patients (1.65%), of which 7/10 boys (70%). At the time of diagnosis, the median age was 10.99 years (3–17.5), and the median BMI was 18.62 kg/m2 (13–22.06). Five patients (50%) were referred for diagnostic processing due to chronic inflammatory bowel disease suspicion, and five patients (56%) due to haematochezia and suspected bleeding polyp. The patients presented with various complaints of which: abdominal pain 4/10 (40%); blood in stool 6/10 (60%); diarrhea 3/10 (30%); and significant weight loss and perianal abscess in one patient. All patients had normal inflammatory parameters (CRP <2.8) and normal hemoglobin values for age (Hb 116-142). The mean duration of symptoms was 6.3 months (0.25 – 18). Parasite analysis of stool was performed in 4 patients (40%) and was negative in all, and perianal impression with adhesive cellophane tape was performed in only one patient, also negative. In all patients, E. vermicularis was confirmed macroscopically. In one patient, vulnerable mucosa reminding of ulcerative colitis (UC) was found along with enterobiasis, and in one patient we found non-specific terminal ileitis. Eosinophilia was found in four patients in intestinal biopsy samples. Following anthelmintic therapy with mebendazole, there was no recurrence of pinworm. One patient was later diagnosed with UC in the follow-up. Conclusion: Enterobius vermicularis is generally considered an innocent parasite, which in most cases causes perianal pruritus, and although it matures and lives in the intestines, severe gastrointestinal symptoms have rarely been reported. E. vermicularis infestation should be considered in patients with hematochezia, the screening of choice is perianal impression with cellophane tape, and the choice of treatment is mebendazole.